Child Trafficking Crimes from an Islamic Legal Perspective: A Study of Decision No. 2207/Pid.Sus/2022 Mdn - Annisa, Annisa (Universitas Islam Negeri Sumatera Utara, 2023)
The crime of child trafficking is a form of crime that violates human rights, especially the rights of children. This crime not only harms the dignity and future of children, but also has a profound negative impact on society. In the perspective of Islamic law, the crime of child trafficking is a very despicable and prohibited act, because Islam upholds the protection of children and upholds justice and human rights. This research aims to analyze court decision number 2207/Pid.Sus/2022 Mdn, relating to the crime of child trafficking, in the context of Islamic law. This research uses a qualitative approach with a normative juridical analysis method of the verdict, and examines how the verdict is in line with the principles of Islamic law. The results show that verdict number 2207/Pid.Sus/2022 Mdn provides punishment to the perpetrator of child trafficking in accordance with applicable laws and regulations. In the perspective of Islamic law, the decision is appropriate because it punishes the perpetrators for offenses committed against children. However, this study also highlights the importance of more assertive and consistent law enforcement to prevent child trafficking crimes in the future. In conclusion, this study emphasizes the need for synergy between positive law and Islamic law in dealing with the crime of child trafficking. In addition, further efforts are needed in the prevention and handling of this crime so that children can be well protected and the community can live in a safe and prosperous environment.